Strategic Decisions in Setting Up Child Rights Impact Assessments - Desmet, Ellen; Op De Beeck, Hanne (Revue générale de droit, 2014)
Establishing a child rights impact assessment (CRIA) requires making strategic choices in regards to scope and process. This article focuses on choices regarding (i) the material scope: for which documents will a CRIA be carried out?; (ii) the personal scope: will a CRIA be done only for children (0-18 years), or be extended towards young adults?; and (iii) the relationship to other instruments and processes: will a CRIA stand alone, or be integrated with other impact assessments? The relation between CRIA and other instruments, such as child(-friendly) budgeting is also discussed. The article illustrates these choices, drawing on an evaluation of the experience of implementing the Child and Youth Impact Report (JoKER) in Flanders (Belgium).